PRICING TO MARKET AND EXCHANGE RATE PASS THROUGH IN THE SRI LANKA TEA EXPORT MARKETS - Sathiyamoorthy, S.; Murugan, P.; Krishnapillai, S. (My University, 2016)
This paper studies the pricing to market strategy across Sri Lankan tea export destinations by examining exchange-rate pass-through into export prices of tea packets, tea bags, tea in bulk, and other forms of tea for ten destination countries from 2003 to 2014. For this purpose, quantity and total value of tea exports were collected from the Export Development Board. Exchange rates in direct quotations (Sri Lankan rupees per a foreign currency) are obtained from Annual Reports published by Central Bank of Sri Lanka.This study employs a linear mixed model in panel data to appropriately capture pricing behaviour of Sri Lankan tea exports to the selected destination markets. The significant negative coefficient of exchange rate indicates that incomplete exchange-rate pass-through occurs for Sri Lankan tea exports. Export prices of tea packets and other forms of tea are adjusted upward by 0.7% and 1.5% for a 10% appreciation of the Sri Lankan rupees relative to the foreign currencies respectively. In other words, Export prices of tea packets and other forms of tea are adjusted downward by 0.7% and 1.5% for a 10% depreciation of the Sri Lankan rupees relative to the foreign currencies respectively. Export prices of tea bags are adjusted upward by 1.7% for a 10% appreciation the Sri Lankan rupees, but this coefficient is significant at 10% level. Coefficient of exchange rate for the tea in bulk is insignificant that indicates that export price of tea in bulk is not adjusted for the appreciation or depreciation of Sri Lankan rupees relative to the foreign currencies. These results indicate that tea exporters persistently exercise non-competitive pricing. This study suggests that tea exporters have been making a considerable effort to expand their international markets and its long run pricing to market strategy appears to work through incomplete exchange-rate pass-through. Expanding market share of tea exports by implementing incomplete exchange-rate pass-through has been a strategically viable plan
Keywords: Pricing to market; Exchange rate pass through; Non-competitive pricing; Linear mixed model